Complete resolution of erythrodermic psoriasis with first-line apremilast monotherapy. Issue 1 (31st January 2019) - Krishnamoorthy, Geetha; Kotecha, Aditya; Pimentel, Jason
Abstract : Erythrodermic psoriasis (EP) is the most serious type of psoriasis with high morbidity and mortality. First-line recommended therapies for EP, cyclosporine and infliximab have significant adverse effects. Cyclosporine increases the risk of hypertension, leucopenia, infections and renal failure. Infliximab increases the risk of reactivation of tuberculosis, hepatitis B and histoplasmosis, and increases risk for hepatitis, autoantibody formation, congestive heart failure, demyelinating disorders, pancytopenia, lymphoma and skin cancer. An effective drug with a much safer side effect profile will be of significant benefit in EP. The phosphodiesterase 4 inhibitor apremilast is U.S Food and Drug Administration (FDA) approved for plaque psoriasis and psoriatic arthritis. Adverse effects of apremilast reported are headache, nausea, diarrhoea, upper respiratory tract infection, potential for depression and weight loss. We report complete and long-standing resolution of EP with first-line apremilast monotherapy. Apremilast may be an effective option with comparatively minor side effects for EP.